Epidemiology of eating disorders in Africa. Issue 6 (November 2016) - van Hoeken, Daphne; Burns, Jonathan K.; Hoek, Hans W.
Abstract : Purpose of review: This is the first review of studies on the epidemiology of eating disorders on the African continent. Recent findings: The majority of articles found through our search did not assess formal diagnoses, but only screened for eating attitudes and behaviors. Only four studies – including only one recent study – provided specific epidemiological data on anorexia nervosa, bulimia nervosa, and/or eating disorder not otherwise specified (EDNOS). No cases of anorexia nervosa according to Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV criteria were found among a total of 1476 (young) females. The combined point-prevalence rate of bulimia nervosa is 0.87% (95% CI 0.22–1.51) and of EDNOS is 4.45% (95% CI 2.74–6.16) in young women in Africa. Summary: The epidemiological study of eating disorders in Africa is still in its infancy. Over time in total four studies providing epidemiological data on specific, formally assessed eating disorders were found. No cases of anorexia nervosa were reported in African epidemiological studies, which concurs with the very low prevalence rates of anorexia nervosa in Latin Americans and in African Americans in the USA. With the DSM-5 criteria for anorexia nervosa, some women in the African studies would have fulfilled the criteria for anorexia nervosa. The prevalence rate of bulimia nervosa in women in Africa is within the range reported for western populations, as well as African Americans and Latin Americans.